Upaya Meningkatkan Pemahaman Konsep Nilai Tempat Bilangan Cacah melalui Media Papan Angka pada Siswa Sekolah Dasar - Nadia Nur Nabilah G; Ibnu Muthi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to improve students’ understanding of the concept of place value of whole numbers through the use of number board media in primary school mathematics learning. The background of this study stems from the fact that many students struggle to distinguish between digits and their place values due to the dominance of conventional, less contextual teaching approaches. This research used the Classroom Action Research (CAR) method conducted in two cycles involving second-grade elementary school students. The findings revealed a significant increase in conceptual understanding after the use of number board media. Students became more active, were able to correctly position digits, and comprehended the meaning of place value more concretely. The implication of this research shows that concrete media such as number boards are effective in strengthening students’ understanding of abstract mathematical concepts in a fun and meaningful way.